2017
DOI: 10.1080/09603123.2017.1415305
|View full text |Cite
|
Sign up to set email alerts
|

Integrative study of cell damage and cancer risk in gas station attendants

Abstract: Gas station attendants are potentially exposed to carcinogenic substances. This study aimed to evaluate chronic occupational exposed gas station attendant's according to genetic parameters and its relationship with cancer predisposition. Forty gas station attendants were recruited and paired with 40 control subjects. Thousand cells from each subject were analyzed counting the number of pyknotic (PYC), karyolitic (KYL), karyorrhetic (KHC), condensed chromatin (CC), binucleated (BN), basal cells (BC), Nuclear bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Several studies failed to prove the short-term PMs exposure as a risk factor that could elevate daily cardiovascular hospital admissions or mortality [ 46 47 ]. One main reason for these inconsistencies is that the exposure-response relationships can be non-linear [ 23 24 25 ]. Moreover our previous study also indicated that this relationship between ASHD mortality and air pollution seemed to be non-linear [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies failed to prove the short-term PMs exposure as a risk factor that could elevate daily cardiovascular hospital admissions or mortality [ 46 47 ]. One main reason for these inconsistencies is that the exposure-response relationships can be non-linear [ 23 24 25 ]. Moreover our previous study also indicated that this relationship between ASHD mortality and air pollution seemed to be non-linear [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…To further detect the gender-based differences in the vulnerability to air pollution, we used the Distributed lag nonlinear models (DLNMs) to explore the seasonal exposure-response relationships (during lag0-7) [ 22 ]. Considering the exposure-response relationships were not always linear or monotonic, we selected a natural spline function whose dfs were chosen according to the minimum unbiased risk estimator (UBRE) value [ 23 24 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Both groups (exposed and control) were submitted to the same procedure for sample collection and preparation. Collection of the oral mucosa and the preparation of slides were performed according to the protocol described by Thomas et al (1), with slight modifications already published by Silveira et al (8) and Filho et al (4). Briefly, buccal mucosa cells were collected by scraping the inner cheek using a sterille swab and placed in 3 ml of saline solution.…”
Section: Methodsmentioning
confidence: 99%
“…Human biomonitoring studies have tried to establish an association between the risk for future diseases and occupational exposure, life style and environmental and nutritional contamination (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In this context, car painting represents a potential occupational hazard, especially due to the known use of benzene, isocyanates, toluene and xylene (12,13).…”
mentioning
confidence: 99%
“…MNs represent chromosomes that have been separated from the mitotic spindle during impaired mitosis and contain a high proportion of centromeric material along with heterochromatin [25] . MNs can also be assessed from exfoliated buccal mucosa cells [26][27][28][29][30][31] or cultures of peripheral blood lymphocytes [32] .…”
Section: Micronucleus Testmentioning
confidence: 99%